2009
DOI: 10.1016/j.arthro.2009.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Lidocaine Potentiates the Chondrotoxicity of Methylprednisolone

Abstract: Intra-articular injections of corticosteroids and local anesthetics are widely used in clinical practice. This in vitro study provides information on the potential effects of these drugs on articular cartilage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
52
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(61 citation statements)
references
References 19 publications
6
52
1
Order By: Relevance
“…However, it is difficult to synthesize these data, because the origin of the investigated chondrocytes, the culture conditions, and the exposure times are distinct. Nevertheless, our data are consistent with that of Seshadri et al [46] who also reported greater cytotoxicity after combined exposure of agents. Other widely used agents for intraarticular osteoarthritis treatment are local anesthetics alleviating pain effectively, yet they may have a cytotoxic action on chondrocytes [7,23,39].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…However, it is difficult to synthesize these data, because the origin of the investigated chondrocytes, the culture conditions, and the exposure times are distinct. Nevertheless, our data are consistent with that of Seshadri et al [46] who also reported greater cytotoxicity after combined exposure of agents. Other widely used agents for intraarticular osteoarthritis treatment are local anesthetics alleviating pain effectively, yet they may have a cytotoxic action on chondrocytes [7,23,39].…”
Section: Discussionsupporting
confidence: 83%
“…The rationale would be that the local anesthetic component acts quickly after administration, it provides fast alleviation of pain, and it may last for up to the point when the steroid component starts to exert its effect. Although it has been reported that steroids and local anesthetics have a strong cytotoxic effect on chondrocytes, concomitant administration of corticosteroids and local anesthetics in osteoarthritis is still a widely used and investigated method [12,27,32,[45][46][47]. Similar to our findings, a recent study revealed a methylprednisolone-lidocaine combination showed a cytotoxic effect on bovine chondrocytes cultured in alginate beads [46].…”
Section: Discussionsupporting
confidence: 81%
“…The investigators concluded that triamcinolone acetonide attenuated the chondrotoxicity of mepivacaine [5]. In contrast, a study using a bovine cartilage found that, although the methylprednisolone showed time-and dose-dependent chondrotoxic effects, the combination of lidocaine and methylprednisolone showed a synergistic chondrocidal effect; there was no single-treatment lidocaine group for direct comparison to methylprednisolone [41]. In our study on human cartilage, triamcinolone caused a substantial loss of chondrocyte viability in the articular plug and monolayer culture groups and was more chondrotoxic than bupivacaine.…”
Section: Discussionmentioning
confidence: 89%
“…In vitro studies suggest chondrotoxicity of local anesthetics and corticosteroids in various animal models [11,12,22,27,32,41]. However, combinational effects of corticosteroids and local anesthetics or the buffering of these agents have not been studied on human cartilage.…”
Section: Discussionmentioning
confidence: 99%
“…Concerns for systemic toxicity have led to new interest in evaluating the anti-inflammatory effects of high molecular weight hyaluronan 17 . Corticosteroid injections have a known anti-inflammatory effect but many formulations also carry concerns for chondrotoxicity, especially when corticosteroids are combined with local anesthetics 18,19 . While injection therapy reduces the risk of systemic toxicity, long-term and sustained bioactivity remains difficult to achieve without incurring substantial local morbidity from repeated injections.…”
Section: Early Diagnosis Enables Early Treatment To Reduce Osteoarthrmentioning
confidence: 99%